2017
DOI: 10.1108/ejm-09-2015-0637
|View full text |Cite
|
Sign up to set email alerts
|

Moving toward settlement: tourism as acculturation practice

Abstract: Purpose The purpose of this paper is to explore the capital-based benefits which arise when acculturating immigrants perform touristic practices, and how these shape their tourism and migration experiences. Design/methodology/approach Grounded in consumer culture theory, this paper draws on theories of capital consumption to inform a hermeneutic analysis of multi-modal depth interviews with Southeast Asian skilled migrants in New Zealand. Findings Domestic touristic practices offer three types of capital-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…With the emergence of some phenomena in rural tourism, such as the tension between people and land and the destruction of rural images, more scholars began to call for a return to the essence of rural tourism. Cruz et al found that rural tourism was seriously damaged, and they regarded the cognition and protection of rural tourism as the essence of rural tourism [ 16 ]. From the viewpoint of tourists' consumption patterns, Muresan et al sought to identify the distinctive rural tourism mode before proposing workable development strategies to support the long-term growth of rural tourism [ 17 ].…”
Section: Related Workmentioning
confidence: 99%
“…With the emergence of some phenomena in rural tourism, such as the tension between people and land and the destruction of rural images, more scholars began to call for a return to the essence of rural tourism. Cruz et al found that rural tourism was seriously damaged, and they regarded the cognition and protection of rural tourism as the essence of rural tourism [ 16 ]. From the viewpoint of tourists' consumption patterns, Muresan et al sought to identify the distinctive rural tourism mode before proposing workable development strategies to support the long-term growth of rural tourism [ 17 ].…”
Section: Related Workmentioning
confidence: 99%
“…Our research argues that locals too experience emotional, behavioral and identity responses as they live with outsiders. Consumer acculturation is a relational and interactive process that entails how one group perceives and adapts in response to contact with the other (Cruz and Buchanan-Oliver, 2017). However, most extant research focuses on the acculturation of the new group (immigrants) to the host group (indigenes).…”
Section: Consumer Acculturationmentioning
confidence: 99%
“…This process explains how individuals keep the features of their own culture while consuming new ones, whereas they introduce a new culture for the ones who would not have the chance to know it. They do so by exercising an acculturation that ends up playing a productive role in consumption flow (Askegaard et al, 2005;Cruz & Buchanan-Oliver, 2017). Accordingly, it is more usual to maintain a native culture in private life (food, music, clothing, celebrations) than to get to know other cultures in public domains (school and work environments, social networks) (Martin, 2012;Peñaloza, 1994) where individuals exercise consumption acculturation by negotiating different cultures (Arends-Tóth & Van de Vijver, 2008;Jamal, 2003;Kizgin et al, 2018).…”
Section: Consumption Acculturationmentioning
confidence: 99%